Rizal : A Modular Approach based on the new CHED Curriculum - Francisco, Virlyn; Francisco, Paul Micah (Manila, 2018)
The main purpose of the book is to encourage the students to treat the course not only as a requirement to finish the degree but to emulate the sacrifices of Jose P. Rizal as a person and as a hero. The saga of Rizal did not stop upon his execution but lives on until this present time when the civil society is looking for a redeemer and standard for a real government.
Keywords: Rizal, Jose